Modified radical mastectomy for intraductal breast carcinoma in a patient with active pulmonary tuberculosis under thoracic epidural anaesthesia - Usha Devi R; Vasantha Kumar K R; Aasthaa Aasthaa; Vinutha D. K; Kavyashree Kavyashree (International Journal of Medical Research and Review, 2016)
The incidence of breast carcinoma is on the rise in Asian countries like India and pulmonary tuberculosis is one of the most common infectious diseases encountered here. Although coexistence of active pulmonary tuberculosis and breast cancer in same patient is rare, it poses a huge challenge to the anaesthetist when patients having the above conditions concomitantly are posted for surgeries like mastectomy. Here we report the anaesthetic management of a case of breast carcinoma with active pulmonary tuberculosis managed successfully under thoracic epidural anaesthesia chosen to avoid major hemodynamic, respiratory and other complications like operation theatre pollution and drug interactions between anti tubercular and anticancer drugs and drugs used for general anesthesia.